2008
DOI: 10.1073/pnas.0709732105
|View full text |Cite
|
Sign up to set email alerts
|

Plant adaptation to fluctuating environment and biomass production are strongly dependent on guard cell potassium channels

Abstract: At least four genes encoding plasma membrane inward K ؉ channels (Kin channels) are expressed in Arabidopsis guard cells. A double mutant plant was engineered by disruption of a major K in channel gene and expression of a dominant negative channel construct. Using the patch-clamp technique revealed that this mutant was totally deprived of guard cell Kin channel (GCKin) activity, providing a model to investigate the roles of this activity in the plant. GCKin activity was found to be an essential effector of sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 30 publications
(49 reference statements)
9
139
0
1
Order By: Relevance
“…The Nobel-Prize-winning work on Shaker channels has furthermore provided a model, based on X-ray crystallography, of K + binding on the outside of the channel that specifically disallows the binding of Na + -according to the model, the ions are bound in their "naked", dehydrated state, and the difference in ionic radii makes it impossible for the smaller Na + ion to bind successfully to the oxygen-enriched "corners" of the channel (Doyle et al 1998;Dreyer and Uozumi 2011). This model is supported by electrophysiological studies on guard cell protoplasts that demonstrate channel conductances with high (more than an order of magnitude larger) K + selectivity over Na + (Schroeder et al 1984(Schroeder et al , 1987Schroeder 1988;Blatt 1992;Müller-Röber et al 1995;Nakamura et al 1995;Véry et al 1995; see also Véry et al 1998;Lebaudy et al 2008). However, given the multiplicity of inward-rectifying K + channels being expressed in guard cells (Szyroki et al 2001), and that some of these have been demonstrated to be capable of mediating Na + fluxes, albeit mostly in other cell types (Golldack et al 2003;Obata et al 2007;Wang et al 2007), routes for high-capacity Na + entry might exist under some conditions that are not currently accounted for in stomatal guard cell models (Fig.…”
Section: Sodium As a Nutrientsupporting
confidence: 54%
“…The Nobel-Prize-winning work on Shaker channels has furthermore provided a model, based on X-ray crystallography, of K + binding on the outside of the channel that specifically disallows the binding of Na + -according to the model, the ions are bound in their "naked", dehydrated state, and the difference in ionic radii makes it impossible for the smaller Na + ion to bind successfully to the oxygen-enriched "corners" of the channel (Doyle et al 1998;Dreyer and Uozumi 2011). This model is supported by electrophysiological studies on guard cell protoplasts that demonstrate channel conductances with high (more than an order of magnitude larger) K + selectivity over Na + (Schroeder et al 1984(Schroeder et al , 1987Schroeder 1988;Blatt 1992;Müller-Röber et al 1995;Nakamura et al 1995;Véry et al 1995; see also Véry et al 1998;Lebaudy et al 2008). However, given the multiplicity of inward-rectifying K + channels being expressed in guard cells (Szyroki et al 2001), and that some of these have been demonstrated to be capable of mediating Na + fluxes, albeit mostly in other cell types (Golldack et al 2003;Obata et al 2007;Wang et al 2007), routes for high-capacity Na + entry might exist under some conditions that are not currently accounted for in stomatal guard cell models (Fig.…”
Section: Sodium As a Nutrientsupporting
confidence: 54%
“…Light induces the expression of GLK1 and GLK2 (23) and ABA decreases the expression of GLK2 in guard cells (39), similar to the behavior of KAT1 and consistent with the movements of stomata. Because an increase in K + in channel activity does not produce additional stomatal opening (21,36,37,40), the open-stomata phenotype of 35S:GLK1/2 plants indicates that GLK1/2 may regulate the expression of genes necessary for stomatal opening other than those for K + in channels (Fig. 3A), which may induce the more-severe closed-stomata phenotype of 35S: GLK1/2-SRDX plants.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the dominant negative form of KAT1 or KAT2 impaired the activity of K + in channels in guard cells and clearly inhibited light-dependent stomata opening (36,37), indicating that the activity of K + in channels in guard cells is essential and might be much higher than the threshold necessary for stomata opening (35)(36)(37)(38). Although the severe closed-stomata phenotype of 35S:GLK1/2-SRDX plants might result from combinatorial effects of multiple genes, we suggest that their closed-stomata phenotype in light conditions was attributable, at least in part, to a decrease in the activity of K + in channels and a reduction of the expression of K + in channel genes in guard cells as shown in aks1 aks2 mutants (21).…”
Section: Discussionmentioning
confidence: 99%
“…One hole was drilled in the lid through which a single plant could grow (44). The plants were grown for 5 weeks (late rosette stage), during which they were watered periodically to keep the whole pot weight constant.…”
Section: Methodsmentioning
confidence: 99%
“…The difference was slightly more pronounced after the light-to-dark transition (29). Whole plants were grown in soil to measure water loss in atpp2ca mutants using individual sealed pots (44). Under constant light, the transpiration rate was reduced slightly (by about 6%) in the atpp2ca mutants (Fig.…”
Section: Atpp2ca Mutants Display a Decreased Transpiration Phenotypementioning
confidence: 99%